Leptin regulation of the p53-HIF1α/PKM2-aromatase axis in breast adipose stromal cells: a novel mechanism for the obesity–breast cancer link - Zahid, H; Subbaramaiah, K; Iyengar, N M; Zhou, X K; Chen, I-C; Bhardwaj, P; Gucalp, A; Morrow, M; Hudis, C A; Dannenberg, A J; Brown, K A (International Journal of Obesity, 2018)
Background/Objectives: Obesity (body mass index (BMI)⩾30 kg m −2 ) is associated with an increased risk of estrogen-dependent breast cancer after menopause. Levels of aromatase, the rate-limiting enzyme in estrogen biosynthesis, are elevated in breast tissue of obese women. Recently, the regulation of aromatase by the p53-hypoxia-inducible factor-1α (HIF1α)/pyruvate kinase M2 (PKM2) axis was characterized in adipose stromal cells (ASCs) of women with Li–Fraumeni Syndrome, a hereditary cancer syndrome that predisposes to estrogen-dependent breast cancer. The current study aimed to determine whether stimulation of aromatase by obesity-associated adipokine leptin involves the regulation of the p53-HIF1α/PKM2 axis. Subjects/Methods: Human breast ASCs were used to characterize the p53-HIF1α/PKM2-aromatase axis in response to leptin. The effect of pharmacological or genetic modulation of protein kinase C (PKC), mitogen-activated protein kinase (MAPK), p53, Aha1, Hsp90, HIF1α and PKM2 on aromatase promoter activity, expression and enzyme activity was examined. Semiquantitative immunofluorescence and confocal imaging were used to assess ASC-specific protein expression in formalin-fixed paraffin-embedded tissue sections of breast of women and mammary tissue of mice following a low-fat (LF) or high-fat (HF) diet for 17 weeks. Results: Leptin-mediated induction of aromatase was dependent on PKC/MAPK signaling and the suppression of p53. This, in turn, was associated with an increase in Aha1 protein expression, activation of Hsp90 and the stabilization of HIF1α and PKM2, known stimulators of aromatase expression. Consistent with these findings, ASC-specific immunoreactivity for p53 was inversely associated with BMI in breast tissue, while HIF1α, PKM2 and aromatase were positively correlated with BMI. In mice, HF feeding was associated with significantly lower p53 ASC-specific immunoreactivity compared with LF feeding, while immunoreactivity for HIF1α, PKM2 and aromatase were significantly higher. Conclusions: Overall, findings demonstrate a novel mechanism for the obesity-associated increase in aromatase in ASCs of the breast and support the study of lifestyle interventions, including weight management, which may reduce breast cancer risk via effects on this pathway.